Analysis of Influence of Soft Ground Treatment by Vacuum Preloading on Adjacent Pile Foundation - ZHOU Qiong; LI Wei; GAO Ying; WANG Jing (Renmin Zhujiang)
In soft ground,the deflection of adjacent pile foundation and the uneven settlement of soil around the piles caused by the surcharge loading is an extremely negative impact on the safety of the bridge.Base on the three-dimensional finite element analysis,and the specific engineering case,this paper calculates the internal force and deformation of the adjacent pile foundation under the treatment of soft ground by the vacuum surcharge preloading and the surcharge preloading,respectively.The results show that the internal force and deformation distribution of the pile foundation under the vacuum surcharge preloading are different from that under the surcharge preloading,and the internal force and deformation of the former case are less than that of the latter case,which indicates that the vacuum preloading has a positive effect on reducing the impact of ground surcharge loading on adjacent pile foundation.